2022
DOI: 10.1021/acs.jmedchem.2c00626
|View full text |Cite
|
Sign up to set email alerts
|

Micromonospora: A Prolific Source of Bioactive Secondary Metabolites with Therapeutic Potential

Abstract: Micromonospora, one of the most important actinomycetes genera, is well-known as the treasure trove of bioactive secondary metabolites (SMs). Herein, together with an in-depth genomic analysis of the reported Micromonospora strains, all SMs from this genus are comprehensively summarized, containing structural features, bioactive properties, and mode of actions as well as their biosynthetic and chemical synthesis pathways. The perspective enables a detailed view of Micromonospora-derived SMs, which will enrich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 331 publications
0
20
0
Order By: Relevance
“…To the best of our knowledge, this is the first application of this strategy in Micromonospora strains, resulting in improving the biosynthesis of complex natural products. Since Micromonospora is one of the most prolific producers of bioactive natural products, , the successful practice of the BGC duplication strategy holds promise to accelerate the discovery and engineering of Micromonospora -derived natural products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first application of this strategy in Micromonospora strains, resulting in improving the biosynthesis of complex natural products. Since Micromonospora is one of the most prolific producers of bioactive natural products, , the successful practice of the BGC duplication strategy holds promise to accelerate the discovery and engineering of Micromonospora -derived natural products.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first application of this strategy in Micromonospora strains, resulting in improving the biosynthesis of complex natural products. Since Micromonospora is one of the most prolific producers of bioactive natural products, 69,70 the successful practice of the BGC duplication strategy holds promise to accelerate the discovery and engineering of Micromonospora-derived natural products. Two engineered strains with improved productivity allowed us to isolate six intact EVNs and the corresponding hydrolyzed analogues in sufficient amounts to allow comprehensive in vitro bioactivity evaluation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…exploration, it is now clear that investigations of marine Micromonosporaceae are likely to unveil NPs that differ from those of terrestrial strains, including both general terrestrial bacterial strains and terrestrial Micromonosporaceae Micromonospora spp. [9, 17, 18]. (This study showed that members of the family Micromonosporaceae were more abundant among cultivated bacteria from tropical ecosystems versus brackish ones.…”
Section: Introductionmentioning
confidence: 97%
“…Pyrroles possess a flat and electron-rich aromatic ring, and their structure is susceptible to electrophilic attack and can also interact with a variety of biomolecules via hydrogen bonds as well as π–π stacking interactions [ 19 ]. Because of their intriguing structures and wide range of biomedical properties, various pyrrole-based compounds have been studied for pharmacological activities [ 16 , 20 , 21 , 22 ]. Streptopyrroles are one of the examples of pyrrole-containing compounds with potent antimicrobial properties and inhibitory activity on the nitrogen regulator II (NRII) histidine kinase from Escherichia coli [ 23 ].…”
Section: Introductionmentioning
confidence: 99%